Case report of a conservative management of cervical esophageal perforation with acrylic glue injection. (July 2018) - Anoldo, P.; Manigrasso, M.; Milone, F.; De Palma, G.D.; Milone, M.
Abstract: Background: perforation of the upper aerodigestive tract is a potentially life-threatening condition. The appropriate treatment of cervical esophageal perforation is still controversial. Case presentation: we report a case of cervical esophageal perforation that was effectively treated by a conservative management with acrylic glue injection. Discussion: the management of cervical esophageal perforations has been controversial and little studied. Various treatment options, including surgical and nonsurgical management have been advocated, and no gold standard surgical treatment has yet been established. Some authors have recommended immediate surgical intervention, especially in penetrating trauma, conversely, several studies support conservative management. Conclusions: we consider that the application of acrylic glue can be considered a promising, minimally invasive therapeutic option in the management of cervical esophageal perforation. However, the sufficient accumulation of similarly treated cases is necessary in order to confirm the efficacy and safety of this treatment modality. Highlights: Perforation of the upper aerodigestive tract is a potentially life-threatening condition. We present the case of a young woman with an iatrogenic cervical esophageal perforation. A conservative management with acrylic glue injection guaranteed a fast recovery. This is the first case reporting the injection of glue into the external fistula opening.